"Um caso de desamor": o debate sobre a estatização do setor de energia elétrica 1956-61 - Silva, Marcelo Squinca da (2009)
This study is about the development of the sector of electric energy in Brazil, focusing on the period of the Varga´s government to the first government of post-64 military dictatorship, led by general Castelo Branco. Its searchs, through analysis of different documents, evidences how the interests of different segments of the national bourgeoisie interacted with each other and with the interests of foreign companies of electric energy operating in the country. This interaction of forces established, during the analysis period, the sprouting of two opposing groups: nationalists and private, whose collisions, ahead the dilemma of to nationalize or not the energy sector, resulted in the creation of the Brazilian Central Electric S/A (Eletrobrás) in 1961. Although its is not the focus of interest to characterize the way that imperialism assumed in Brazil, it is inevitable, by the analytical prism used, to make references to the concepts of hyperlate capitalist development, atrophic capital, monopoly and other categories related, to the context of disputes locked related to the electricity sector